2014
DOI: 10.17221/7794-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cadmium on the level of hepatic metallothioneins, essential elements, and selected enzymes in the experimental rat model

Abstract: ABSTRACT:The response of different strains of laboratory rats (Rattus norvegicus L.) on both acute (via intraperitoneal injection) and chronic (via drinking water and/or diet) cadmium intoxication was investigated in the model study. The rat strains Long Evans (LE), Spontaneously hypertensive rat (SHR), and Brown Norway (BN) were tested and compared, and total Cd levels and metallothionein (MT) concentrations were determined in the liver of experimental animals. The liver MT concentrations were determined by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Cd mainly accumulates in the liver and sometimes in the kidney (Cinar et al, 2011;Karmakar et al, 2000) due to the binding of Cd to metallothionein (Hardej and Trombetta, 2004). Absorption and in turn tissue accumulation of dietary Cd is mainly influenced by dose, age, gender, species, length of the application and nutritional status, as well as by dietary intake of other elements that may interact with Cd (Al-Waeli et al, 2013;Zídková et al, 2014). In agreement with our results, Leach et al (1979) revealed that liver in the treated chicken with dietary Cd was accumulated by higher concentration of Cd than muscles.…”
Section: Table 10supporting
confidence: 88%
See 1 more Smart Citation
“…Cd mainly accumulates in the liver and sometimes in the kidney (Cinar et al, 2011;Karmakar et al, 2000) due to the binding of Cd to metallothionein (Hardej and Trombetta, 2004). Absorption and in turn tissue accumulation of dietary Cd is mainly influenced by dose, age, gender, species, length of the application and nutritional status, as well as by dietary intake of other elements that may interact with Cd (Al-Waeli et al, 2013;Zídková et al, 2014). In agreement with our results, Leach et al (1979) revealed that liver in the treated chicken with dietary Cd was accumulated by higher concentration of Cd than muscles.…”
Section: Table 10supporting
confidence: 88%
“…In the present study, all levels of dietary Cd resulted in significant increases in the Cd concentration of muscles and liver in comparison with control. The distribution of Cd among organs of animals differs depending on the chemical form of administered Cd and the duration of exposure (Zídková et al, 2014). Cd mainly accumulates in the liver and sometimes in the kidney (Cinar et al, 2011;Karmakar et al, 2000) due to the binding of Cd to metallothionein (Hardej and Trombetta, 2004).…”
Section: Table 10mentioning
confidence: 99%
“…The intervention program (1980–2012) involved soil replacement in paddy fields, and since then, the Cd levels in rice grains have significantly declined [73, 74]. However, due to accumulation of Cd in the kidneys and its long biological half life promoted by binding to metallothioneins [75], new cases of itai-itai diseases are being diagnosed even today [73, 74]. Furthermore, as reported by most recent epidemiologic studies, low environmental Cd exposures are also linked with adverse health effects in humans.…”
Section: Cadmium As a Toxicantmentioning
confidence: 99%